2014
DOI: 10.3892/etm.2014.1868
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ and its pathway-associated gene expression in the vaginal tissue of premenopausal females with pelvic organ prolapse

Abstract: Interferon (IFN)-γ is a potent proinflammatory molecule. However, few studies have investigated the expression levels of IFN-γ during pelvic organ prolapse (POP). In the present study, the expression levels and tissue localization of IFN-γ and its pathway-associated genes were detected in the vaginal walls of premenopausal females with POP and asymptomatic controls using quantitative polymerase chain reaction and immunohistochemistry. When compared with the matched controls, an 8.6-fold increase in IFN-γ, 3.8-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 18 publications
1
10
0
2
Order By: Relevance
“…A previous study found an increase gene in patients with POP compared to asymptomatic controls. 57 Zhao et al 58 and granulocytes (IL16, CCL8) in human vaginal tissue following LET, while G-CSF is involved in proliferation and differentiation of haematopoietic precursors of granulocytes and in production of other cytokines in vivo (i.e. TNF-α).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study found an increase gene in patients with POP compared to asymptomatic controls. 57 Zhao et al 58 and granulocytes (IL16, CCL8) in human vaginal tissue following LET, while G-CSF is involved in proliferation and differentiation of haematopoietic precursors of granulocytes and in production of other cytokines in vivo (i.e. TNF-α).…”
Section: Discussionmentioning
confidence: 99%
“…Data presented as mean ± SEM, N = 12 levels of IL-6, CCL2, CXCL1, CXCL2 and CXCR4 gene in patients with POP compared to asymptomatic controls 57. Zhao et al58 observed an increase in the expression of IFN-γ and its receptors IFNGR1 and IFNGR2 in vaginal tissue of pre-menopausal women with POP, suggesting that there is an association of inflammatory cytokines (i.e. IFN-γ) and POP.…”
mentioning
confidence: 99%
“…On the other hand, there were a variety of immune related GO terms up-regulated in multiple pelvic floor tissues of POP patients and mice model, indicating a general inflammatory environment in the pelvic floor. Potentially more relevant to our results is the finding by BING ZHAO et al showing a high mRNA expression of IFNγ, IFNGR and IFNGR2 in the uterine tissues of POP patients, and the mRNA expression of genes involved in signaling pathway JAK-STAT was up-regulated which participate in the activation of IFNγ [ 42 ]. In addition, Yeo Jung Moon and Sang Wook Bai et al found a high expression of IL5 in the sacral ligament in POP patient [ 43 ].…”
Section: Discussionmentioning
confidence: 71%
“…Активность перечисленных генов определялась путем анализа периферической крови, доступность этого материала для анализа делает диагностику в большей степени простой и быстрой. В качестве еще одного субстрата для исследования могут выступать крестцово-маточные связки [42][43][44][45][46][47][48][49][50][51] и гораздо реже биоптат стенки влагалища [48,49,52,53]. Зачастую именно крестцово-маточные связки вовлечены в патогенез синдрома слабости тазового дна, поэтому именно эти структуры изучаются на наличие нарушений, связанных с дезорганизацией соединительной ткани [54].…”
unclassified
“…В качестве биоптата могут выступать и ткани влагалища. В исследованиях была доказана связь пролапса с некоторыми маркерами: интерфероном гамма, его рецепторами 1 и 2 (диагностический метод -ПЦР) [49], экспрес-сией гена BMP1 (диагностический метод -ПЦР) [52], экспрессией коллагена 1 и 3, фактора роста тромбоцитов, MMP3 (диагностический метод -иммуногистохимия) [53], уровнем HIF-1-альфа в стромальных клетках ткани влагалища (диагностический метод -иммуногистохимия) [56]. Надо отметить, что уровень HIF-1-альфа оценивался также в крестцово-маточных связках, и вновь была обнаружена ассоциация данного предиктора с этиологией ПТО [57,58].…”
unclassified